D-NiFe / DMBD-Fc catalyst based on double-defect engineering strategy as well as preparation method and application of D-NiFe / DMBD-Fc catalyst

By using the double defect engineering strategy to prepare the D-NiFe/DMBD-Fc catalyst in the electrolytic hydrogen production process, the problems of slow oxygen evolution reaction rate and poor stability of precious metal catalysts are solved, and efficient and stable catalytic performance is achieved, reducing the The cost of hydrogen production has the potential for industrial application.

CN119243247APending Publication Date: 2025-01-03SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411373743.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During the existing process of electrolytic hydrogen production, the rate of the oxygen evolution reaction (OER) step is slow, resulting in low electrolytic water efficiency and high hydrogen production cost. Precious metal catalysts such as IrO2 and RuO2 are not suitable for low reserves, high costs and poor stability. Industrial production, the development and utilization of non-precious metal catalysts are urgently developed and utilized.

Method used

D-NiFe/DMBD-Fc catalyst prepared based on double defect engineering strategy is used to introduce defective ligands and regulate the electronic structure using alkali etching technology to form a catalyst with double defects, which is used to electrocatalyze oxygen production, improve catalytic activity and stability.

Benefits of technology

It has achieved efficient catalytic activity and good stability, can replace the precious metal catalyst RuO2, reduce the cost of hydrogen production, and shows a wide range of application prospects in the field of electrocatalytic water decomposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243247A_ABST
    Figure CN119243247A_ABST
Patent Text Reader

Abstract

The invention discloses a D-NiFe / DMBD-Fc catalyst based on a double-defect engineering strategy as well as a preparation method and application of the D-NiFe / DMBD-Fc catalyst. The preparation method comprises the following steps: dissolving a nickel source and an iron source in water, and uniformly stirring and mixing to obtain a mixed solution 1; dissolving an organic ligand 2, 5-dimercaptoterephthalic acid and ferrocenecarboxylic acid in N, N-dimethylacetamide, and carrying out ultrasonic treatment until the organic ligand is dissolved to obtain a mixed solution 2; dropwise adding the obtained mixed solution 1 into the mixed solution 2, and ultrasonically mixing uniformly to obtain a mixed solution 3; placing foamed nickel in the obtained mixed solution 3, and carrying out hydrothermal reaction to obtain foamed nickel loaded with a precursor product; and putting the obtained foamed nickel loaded with the precursor product into an ethanol solution of alkali, and carrying out etching reaction to obtain the D-NiFe / DMBD-Fc catalyst based on the double-defect engineering strategy. The prepared catalyst is used for electro-catalysis oxygen evolution reaction and has efficient electro-catalysis activity and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy nanomaterials, and in particular to a D-NiFe / DMBD-Fc catalyst based on a double defect engineering strategy, and a preparation method and application thereof. Background Art

[0002] Hydrogen energy is considered to be the most ideal energy carrier due to its high combustion calorific value and pollution-free products. At present, hydrogen production by water electrolysis has been widely studied because of its wide source of water and relatively pure products. However, among the two half reactions of water electrolysis, the oxygen evolution reaction (OER) is a relatively slow reaction involving four-electron transfer. The rate of this reaction step seriously restricts the efficiency of water electrolysis and increases the cost of hydrogen production. Therefore, the design and development of efficient and stable catalysts is the key to breaking this constraint and the key to the industrialization of this technology. Up to now, some precious metal-based catalysts, such as IrO2, RuO2, etc., are considered to be excellent OER reaction catalysts because of their excellent electrochemical activity in OER reactions. However, due to their low reserves, high cost and poor stability, they are not conducive to industrial production. Therefore, the development and utilization of non-precious metal catalysts is very necessary.

[0003] In recent years, metal organic frameworks (MOFs) have been widely studied in the fields of energy storage and electrocatalysis due to their large surface area, high porosity and flexible and adjustable structure. However, their poor conductivity and stability, low electrocatalytic activity and unstable structure after reaction limit their application. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a D-NiFe / DMBD-Fc catalyst based on a dual defect engineering strategy and a preparation method and application thereof.

[0005] The present invention proposes to use some non-bridging organic ligands to replace some bridging connectors to create defects to regulate the electronic structure of MOFs material NiFe / DMBD, and further create defects through alkaline etching, and successfully prepare a D-NiFe / DMBD-Fc catalyst with double defects. First, prepare NiFe / DMBD-Fc containing defective ligands, and adjust the amount and proportion of organic ligands. Then, the successfully prepared NiFe / DMBD-Fc is placed in an alkaline ethanol solution for etching, and the obtained D-NiFe / DMBD-Fc is directly used as a catalyst for electrocatalytic oxygen production.

[0006] The purpose of the present invention is achieved by at least one of the following technical solutions.

[0007] A method for preparing a D-NiFe / DMBD-Fc catalyst based on a dual defect engineering strategy comprises the following steps:

[0008] (1) dissolving a nickel source and an iron source in water, stirring and mixing uniformly to obtain a mixed solution 1;

[0009] (2) dissolving organic ligands 2,5-dimercaptoterephthalic acid and ferrocenecarboxylic acid in N,N-dimethylacetamide, and performing ultrasound until the organic ligands are dissolved to obtain a mixed solution 2;

[0010] (3) adding the mixed solution 1 obtained in step (1) dropwise into the mixed solution 2 obtained in step (2), and mixing by ultrasonication to obtain a mixed solution 3;

[0011] (4) placing the nickel foam in the mixed solution 3 obtained in step (3), performing a hydrothermal reaction, and transferring the mixture to a high-pressure reactor to obtain a nickel foam loaded with a precursor product;

[0012] (5) placing the nickel foam loaded with the precursor product obtained in step (4) in an alkaline ethanol solution, performing an etching reaction, and obtaining a D-NiFe / DMBD-Fc catalyst based on a dual defect engineering strategy.

[0013] Furthermore, the nickel source in step (1) is nickel chloride (NiCl2·6H2O), and the iron source is ferric chloride (FeCl3);

[0014] Furthermore, in the mixed solution 1 of step (1), the concentration of the nickel source is 0.05-0.3 mM, and the concentration of the iron source is 0.05-0.08 mM;

[0015] Preferably, in the mixed solution 1 of step (1), the concentration of the nickel source is 0.2 mM, and the concentration of the iron source is 0.06 mM;

[0016] Furthermore, the stirring time in step (1) is 20 to 60 minutes.

[0017] Furthermore, the molar ratio of nickel to iron in the nickel source and the iron source in step (1) is 4:1 to 2:1.

[0018] Furthermore, in the mixed solution 2 of step (2), the concentration of 2,5-dimercaptoterephthalic acid is 0.05-0.3 mM, and the concentration of ferrocenecarboxylic acid is 0.01-0.05 mM.

[0019] Preferably, in the mixed solution 2 of step (2), the concentration of 2,5-dimercaptoterephthalic acid is 0.1 mM, and the concentration of ferrocenecarboxylic acid is 0.03 mM;

[0020] Furthermore, in step (2), the molar ratio of 2,5-dimercaptoterephthalic acid to ferrocenecarboxylic acid is 10:3 to 10:5.

[0021] Furthermore, the molar ratio of nickel to 2,5-dimercaptoterephthalic acid in the mixed solution 3 of step (3) is 1:1 to 3:1.

[0022] Furthermore, the temperature of the hydrothermal reaction in step (4) is 120 to 160° C., and the time of the hydrothermal reaction is 2 to 5 hours;

[0023] Preferably, the temperature of the hydrothermal reaction in step (4) is 150° C., and the time of the hydrothermal reaction is 3 h.

[0024] Furthermore, the product obtained after the hydrothermal reaction in step (4) is washed three times with ethanol and deionized water respectively, and placed in a vacuum drying oven to dry for later use.

[0025] Furthermore, the nickel foam in step (4) is pretreated before use; the pretreatment method comprises: placing the nickel foam in acetone solution, hydrochloric acid solution, ethanol solution and deionized water in sequence, ultrasonically cleaning to remove oil, impurities and surface oxide film, and then vacuum drying for standby use.

[0026] Furthermore, the alkali in step (5) is potassium hydroxide; the concentration of the alkali ethanol solution is 0.35-0.75M, and the etching reaction time is 9-15h.

[0027] Preferably, the concentration of the alkali ethanol solution in step (5) is 0.5 M, and the etching reaction time is 12 h.

[0028] Furthermore, the product obtained after the etching reaction in step (5) is washed three times with ethanol and deionized water respectively, and placed in a vacuum drying oven to dry for later use.

[0029] The above-mentioned preparation method prepares the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy.

[0030] The above-mentioned D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy is applied in electrocatalytic oxygen production.

[0031] The invention adopts a defect manufacturing method to prepare a D-NiFe / DMBD-Fc catalyst, and utilizes the introduction of defective ligands and alkaline etching to regulate the electronic structure of NiFe / DMBD. The obtained D-NiFe / DMBD-Fc catalyst is used for electrocatalytic oxygen production and has good catalytic properties.

[0032] The present invention introduces defective ligands into MOFs materials, and replaces part of the bridge connectors with some non-bridge organic ligands, thereby changing the coordination environment, playing a role in regulating the electronic structure of NiFe / DMBD, and constructing a defective MOFs material NiFe / DMBD-Fc catalyst with abundant unsaturated metal sites without affecting the crystallinity and porosity of the material. Further, using an alkaline etching strategy, a D-NiFe / DMBD-Fc catalyst with double defects is prepared, and its metal-oxygen bond (MO) bond is destroyed by etching with an alkaline ethanol solution, generating a large number of open unsaturated metal sites and oxygen vacancies. At the same time, due to the increase in alkalinity around the metal (Ni, Fe) center and the introduction of K cations outside the framework, the conductivity of the catalyst is improved, thereby enhancing the conductivity of the material. The catalytic performance and stability of the material are good. The specific process of preparing the D-NiFe / DMBD-Fc catalyst with double defects is to first grow NiFe / DMBD-Fc on a conductive substrate nickel foam by a hydrothermal method, then use an ethanol solution of potassium hydroxide as an etching solution, and immerse the prepared NiFe / DMBD-Fc, and obtain a defective D-NiFe / DMBD-Fc catalyst after several hours of alkaline solution etching. The non-precious metal catalyst prepared by the method of the present invention is applied to electrocatalytic oxygen evolution, and has high catalytic activity and good stability. The catalytic material has been proven to be able to replace RuO2, a commercial precious metal catalyst with the best catalytic activity in the currently recognized oxygen evolution reaction, and is expected to realize industrialized water electrolysis to produce hydrogen, thereby greatly reducing the cost of hydrogen production.

[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0034] (1) The present invention adopts a simple hydrothermal method and alkaline etching to prepare a D-NiFe / DMBD-Fc catalyst based on a double-defect strategy, and the catalytic performance of the catalyst containing defective ligands and after alkaline etching is significantly improved; the present invention uses non-precious metal-based catalysts to replace the commonly used precious metal catalysts on the market, thereby reducing the cost of the catalyst.

[0035] (2) The D-NiFe / DMBD-Fc catalyst prepared by the present invention has a low overpotential, exhibits good catalytic performance and stability, and has broad application prospects in the field of electrocatalytic water decomposition. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a scanning electron microscope (SEM) image of the MOFs material NiFe / DMBD of Example 1;

[0037] Figure 2 This is a scanning electron microscope (SEM) image of NiFe / DMBD-Fc of the single defect strategy in Example 2;

[0038] Figure 3 This is a scanning electron microscope (SEM) image of D-NiFe / DMBD of the single defect strategy in Example 3;

[0039] Figure 4 This is a scanning electron microscope (SEM) image of D-NiFe / DMBD-Fc of the double defect strategy of Example 4;

[0040] Figure 5 X-ray diffraction (XRD) diagrams of the MOFs material NiFe / DMBD of Example 1, Example 2, Example 3 and Example 4 of the present invention;

[0041] Figure 6 This is the X-ray photoelectron spectroscopy (XPS) diagram of D-NiFe / DMBD-Fc of the double defect strategy of Example 4;

[0042] Figure 7 The electron paramagnetic resonance (EPR) spectra of Example 1, Example 2, Example 3 and Example 4 are shown;

[0043] Figure 8 The linear sweep voltammogram (LSV) of the oxygen evolution reaction of the MOFs material NiFe / DMBD of Example 1 and Example 2, Example 3 and Example 4 of the present invention;

[0044] Fig. 9 The D-NiFe / DMBD-Fc of the dual defect strategy of Example 4 of the present invention is at 50 mA·cm -2 Chronopotentiometry curve for 40 h at a current density of ;

[0045] Fig.10 Energy dispersive X-ray spectrum (EDX) of D-NiFe / DMBD-Fc of the double defect strategy of Example 4;

[0046] Fig.11 The linear sweep voltammograms (LSV) of oxygen evolution reactions of Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 4, Comparative Example 4 and Comparative Example 5 of the present invention are shown. DETAILED DESCRIPTION

[0047] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0048] The pretreatment method of nickel foam used in the following examples is:

[0049] The selected nickel foam (2cm×3cm) with a purity of 99.9% was placed in acetone solution, hydrochloric acid solution, ethanol solution and deionized water in turn, ultrasonically cleaned to remove surface oil, impurities, oil and surface oxide film, etc., and then vacuum dried for use.

[0050] The electrochemical performance test characterization (linear voltammetric sweep test) method of the catalysts prepared in the following examples and comparative examples is:

[0051] The catalyst samples prepared in Example 1, Example 2, Example 3, Example 4, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were cut into pieces with a size of 1 cm. 2 The size of was used as the working electrode for linear voltammetric sweep test.

[0052] All electrochemical measurements were performed at room temperature in 1.0 M KOH;

[0053] In a three-electrode system, a series of prepared catalysts were used as working electrodes, 1×1 cm platinum electrodes were used as counter electrodes, and Ag / AgCl electrodes were used as reference electrodes. The test was carried out in a 1 mol / L potassium hydroxide solution. Before the test, 40 cycles of cyclic voltammetry scanning (CV) were performed to activate and stabilize the catalyst, and magnetic stirring was used to prevent the generated bubbles from gathering on the catalyst surface and affecting subsequent reactions. Subsequently, the OER properties of the samples were measured using linear voltammetry scanning (LSV), with a scan rate of 5 mV·s -1 , the scanning range is 1.023 to 1.823 V vs RHE.

[0054] Example 1

[0055] A method for preparing a NiFe / DMBD catalyst comprises the following steps:

[0056] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligand 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) was dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligand was dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use, and the obtained product was NiFe / DMBD.

[0057] Example 2

[0058] A method for preparing a NiFe / DMBD-Fc catalyst based on a single defect strategy comprises the following steps:

[0059] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligands 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) and ferrocenecarboxylic acid (Fc) (0.03mM) were dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligands were dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use, and the obtained product was NiFe / DMBD-Fc.

[0060] Example 3

[0061] A method for preparing a D-NiFe / DMBD catalyst based on a single defect strategy comprises the following steps:

[0062] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligand 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) was dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligand was dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use.

[0063] Next, a 0.5M potassium hydroxide ethanol solution was prepared, and the nickel foam with the product grown in the previous step was immersed in it, and the alkali etching reaction was carried out for 12 hours. Then, the nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60°C for 12 hours. The final black nickel foam loaded with the product was D-NiFe / DMBD.

[0064] Example 4

[0065] A method for preparing a D-NiFe / DMBD-Fc catalyst based on a dual defect strategy comprises the following steps:

[0066] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligands 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) and ferrocenecarboxylic acid (Fc) (0.03mM) were dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligands were dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use, and the obtained product was NiFe / DMBD-Fc.

[0067] Next, a 0.5M potassium hydroxide ethanol solution was prepared, and the nickel foam with the product grown in the previous step was immersed in it, and the alkali etching reaction was carried out for 12 hours. The nickel foam with the product after the reaction was then rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60°C for 12 hours. The final black nickel foam loaded with the product was D-NiFe / DMBD-Fc.

[0068] Comparative Example 1

[0069] A method for preparing a D-NiFe / DMBD-Fc catalyst based on a dual defect strategy comprises the following steps:

[0070] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligands 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) and ferrocenecarboxylic acid (Fc) (0.02mM) were dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligands were dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use, and the obtained product was NiFe / DMBD-Fc.

[0071] Next, a 0.5M potassium hydroxide ethanol solution was prepared, and the nickel foam with the product grown in the previous step was immersed in it, and the alkali etching reaction was carried out for 12 hours. The nickel foam with the product after the reaction was then rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60°C for 12 hours. The final black nickel foam loaded with the product was D-NiFe / DMBD-Fc.

[0072] Comparative Example 2

[0073] A method for preparing a D-NiFe / DMBD-Fc catalyst based on a dual defect strategy comprises the following steps:

[0074] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligands 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) and ferrocenecarboxylic acid (Fc) (0.025mM) were dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligands were dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use, and the obtained product was NiFe / DMBD-Fc.

[0075] Next, a 0.5M potassium hydroxide ethanol solution was prepared, and the nickel foam with the product grown in the previous step was immersed in it, and the alkali etching reaction was carried out for 12 hours. The nickel foam with the product after the reaction was then rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60°C for 12 hours. The final black nickel foam loaded with the product was D-NiFe / DMBD-Fc.

[0076] Comparative Example 3

[0077] A method for preparing a D-NiFe / DMBD-Fc catalyst based on a dual defect strategy comprises the following steps:

[0078] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligands 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) and ferrocenecarboxylic acid (Fc) (0.05mM) were dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligands were dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use, and the obtained product was NiFe / DMBD-Fc.

[0079] Next, a 0.5M potassium hydroxide ethanol solution was prepared, and the nickel foam with the product grown in the previous step was immersed in it, and the alkali etching reaction was carried out for 12 hours. The nickel foam with the product after the reaction was then rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60°C for 12 hours. The final black nickel foam loaded with the product was D-NiFe / DMBD-Fc.

[0080] Comparative Example 4

[0081] A method for preparing a D-NiFe / DMBD-Fc catalyst based on a dual defect strategy comprises the following steps:

[0082] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligands 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) and ferrocenecarboxylic acid (Fc) (0.1mM) were dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligands were dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use, and the obtained product was NiFe / DMBD-Fc.

[0083] Next, a 0.5M potassium hydroxide ethanol solution was prepared, and the nickel foam with the product grown in the previous step was immersed in it, and the alkali etching reaction was carried out for 12 hours. The nickel foam with the product after the reaction was then rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60°C for 12 hours. The final black nickel foam loaded with the product was D-NiFe / DMBD-Fc.

[0084] Comparative Example 5

[0085] A method for preparing a D-NiFe / DMBD-Fc catalyst based on a dual defect strategy comprises the following steps:

[0086] NiCl2·6H2O (0.2mM) and FeCl3 (0.06mM) were dissolved in 12mL deionized water and stirred for 50min, which was called solution A. The organic ligands 2,5-dimercaptoterephthalic acid (DMBD) (0.1mM) and ferrocenecarboxylic acid (Fc) (0.2mM) were dissolved in 12mL N,N-dimethylacetamide and ultrasonicated until the organic ligands were dissolved, which was called solution B. Solution A was added dropwise to solution B and ultrasonicated until the solution was uniform, which was called solution C. The mixed solution C was placed in a high-pressure reactor, and the pre-treated nickel foam was also immersed in the reactor, and the reaction was carried out at a reaction temperature of 150℃ for 3h. The nickel foam with the product after the reaction was rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60℃ for 12h for use, and the obtained product was NiFe / DMBD-Fc.

[0087] Next, a 0.5M potassium hydroxide ethanol solution was prepared, and the nickel foam with the product grown in the previous step was immersed in it, and the alkali etching reaction was carried out for 12 hours. The nickel foam with the product after the reaction was then rinsed with anhydrous ethanol and deionized water for multiple times, and vacuum dried at 60°C for 12 hours. The final black nickel foam loaded with the product was D-NiFe / DMBD-Fc.

[0088] Catalyst characterization and performance testing:

[0089] (1) The catalysts prepared in Examples 1-4 were characterized by morphology, and the results were as follows:

[0090] The morphology of the products obtained in Examples 1-4 was analyzed by scanning electron microscopy (SEM). Figure 1-4 As shown, the introduction of defective ligands has little effect on the morphology of the original NiFe / DMBD, which grows a uniform nanosheet array. With the etching of alkali, we found that the sheet-like morphology has rough wrinkles on the outside, which means that the catalyst has more exposed specific surface area, which is beneficial to the catalytic reaction.

[0091] (2) The catalysts prepared in Examples 1-4 were subjected to structural characterization, and the results were as follows:

[0092] The structures of the products obtained in Examples 1-4 were analyzed by X-ray diffraction (XRD). Figure 5As shown in the figure, the introduction of defective ligand ferrocene carboxylic acid did not change the original MOFs structure. Some exposed characteristic peaks had a slight negative shift, indicating that the introduction of defective ligands played an electronic regulation role. The structure of the catalyst after etching did not change significantly, indicating that the etching treatment did not destroy the crystal structure, but the intensity of some peaks was weakened, and the peak position was also slightly negatively shifted relative to the material before etching. The reason may be that some metal-oxygen bonds connecting the metal oxide layer and the organic ligand are broken, weakening the interaction between adjacent layers. This increases the space of the metal oxide layer and expands the framework at the same time.

[0093] (3) The catalyst prepared in Example 4 was characterized by elemental composition and chemical state, and the results were as follows:

[0094] The surface element composition and chemical state of the double-defect D-NiFe / DMBD-Fc catalyst in Example 4 were characterized by X-ray photoelectron spectroscopy (XPS). Figure 6 As shown, characteristic peaks of Ni, Fe, O, and S elements can be seen, indicating that the D-NiFe / DMBD-Fc catalyst was successfully synthesized.

[0095] (4) The catalysts prepared in Examples 1-4 were subjected to vacancy defect characterization, and the results were as follows:

[0096] The catalysts prepared in Examples 1-4 were subjected to electron paramagnetic resonance (EPR) testing, and the results were as follows: Figure 7 As shown, the oxygen vacancy content of the defect-free MOFs material (Example 1) is relatively low, and with the introduction of defective ligands (Example 2), the vacancies increase significantly, and the characteristic peaks of the samples are more obvious. After alkali etching, due to the breakage of the metal-oxygen bond, the number of oxygen vacancies increases significantly, and the characteristic peaks are most significant (Examples 3 and 4).

[0097] (5) The catalysts prepared in Examples 1-4 were subjected to OER electrochemical performance test characterization, and the results are as follows:

[0098] The electrochemical performance of the catalysts of Examples 1-4 was tested and characterized by linear voltammetry (LSV). Figure 8 As shown, defect-free MOFs catalysts have a larger overpotential than defective catalysts. With the introduction of defective ligand Fc, the electronic structure of the catalyst is adjusted, so that its reaction energy barrier is reduced, and it exhibits a relatively small overpotential in the OER catalytic reaction. Further, more defects are created by alkaline etching. The results show that the electrocatalytic performance of the D-NiFe / DMBD-Fc catalyst with double defects is greatly improved.

[0099] The catalysts of Examples 1-4 were subjected to oxygen evolution reaction at 100 mA·cm -2At a current density of , the overpotential data are as follows:

[0100] Example 1: Oxygen evolution reaction 100mA·cm -2 At a current density of , the overpotential is about 300 mV.

[0101] Example 2: Oxygen evolution reaction 100 mA·cm -2 At a current density of , the overpotential is about 280 mV.

[0102] Example 3: Oxygen evolution reaction 100 mA·cm -2 At a current density of , the overpotential is about 288 mV.

[0103] Example 4: Oxygen evolution reaction 100 mA·cm -2 At a current density of , the overpotential is about 244 mV.

[0104] It can be seen that the introduction of defective ligand Fc reduces the overpotential by 20mV; the introduction of alkaline etching defects reduces the overpotential by 12mV; the simultaneous introduction of defective ligand Fc and alkaline etching defects reduces the overpotential by 56mV, indicating that both defective ligand Fc and alkaline etching defects can reduce the overpotential, and that defective ligand Fc and alkaline etching defects have a synergistic effect, and the simultaneous introduction of both reduces the overpotential more significantly.

[0105] (6) The stability of the oxygen evolution reaction of the double-defect D-NiFe / DMBD-Fc catalyst of Example 4 was tested by chronopotentiometry:

[0106] The chronopotentiometry test results of the catalyst in Example 4 are as follows: Fig. 9 The results show that at a current density of 50 mA cm -2 Under the condition of high current density, the performance of the D-NiFe / DMBD-Fc catalyst (i.e., a D-NiFe / DMBD-Fc catalyst based on double defects in Example 4 as an oxygen evolution reaction catalyst) remains stable for up to 200 hours, and there is no obvious fluctuation in voltage, indicating that the D-NiFe / DMBD-Fc catalyst based on double defects can maintain stable OER catalysis at high current density and has good stability.

[0107] (7) The catalyst prepared in Example 4 was subjected to energy dispersive X-ray spectroscopy (EDX) testing, and the results were as follows:

[0108] Its EDX diagram is shown in Figure 10. Through EDX testing, we determined the presence and content of Ni, Fe, O, S, and K elements, among which Ni accounts for 36.78%, Fe accounts for 1.15%, O accounts for 16.29%, S accounts for 1.83%, K accounts for 0.69%, and the rest is C.

[0109] (8) The catalysts prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5 were subjected to OER electrochemical performance test (LSV) characterization, and the results are as follows:

[0110] By adjusting the molar ratio of the organic ligand 2,5-dimercaptoterephthalic acid and ferrocenecarboxylic acid, we successfully screened out the catalyst with the best catalytic performance under the optimal feed ratio, such as Fig.11 As shown, when the molar ratio of the organic ligand 2,5-dimercaptoterephthalic acid and ferrocenecarboxylic acid is the ratio of Example 4, the prepared catalyst has the minimum oxygen evolution overpotential.

[0111] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a D-NiFe / DMBD-Fc catalyst based on a dual defect engineering strategy, characterized in that: The steps include: (1) dissolving a nickel source and an iron source in water, stirring and mixing uniformly to obtain a mixed solution 1; (2) dissolving organic ligands 2,5-dimercaptoterephthalic acid and ferrocenecarboxylic acid in N,N-dimethylacetamide, and performing ultrasound until the organic ligands are dissolved to obtain a mixed solution 2; (3) adding the mixed solution 1 obtained in step (1) dropwise into the mixed solution 2 obtained in step (2), and mixing by ultrasonication to obtain a mixed solution 3; (4) placing the nickel foam in the mixed solution 3 obtained in step (3) for hydrothermal reaction to obtain a nickel foam loaded with the precursor product; (5) placing the nickel foam loaded with the precursor product obtained in step (4) in an alkaline ethanol solution, performing an etching reaction, and obtaining a D-NiFe / DMBD-Fc catalyst based on a dual defect engineering strategy.

2. The method for preparing the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy according to claim 1, characterized in that: The nickel source in step (1) is nickel chloride, and the iron source is ferric chloride; In step (1), the concentration of the nickel source in the mixed solution 1 is 0.05-0.3 mM, and the concentration of the iron source is 0.05-0.08 mM; The stirring time in step (1) is 20 to 60 minutes.

3. The method for preparing the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy according to claim 1, characterized in that: The molar ratio of nickel to iron in the nickel source and the iron source in step (1) is 4:1 to 2:

1.

4. The method for preparing the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy according to claim 1, characterized in that: In the mixed solution 2 of step (2), the concentration of 2,5-dimercaptoterephthalic acid is 0.05-0.3 mM, and the concentration of ferrocenecarboxylic acid is 0.01-0.05 mM.

5. The method for preparing the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy according to claim 1, characterized in that: The molar ratio of 2,5-dimercaptoterephthalic acid to ferrocenecarboxylic acid in step (2) is 10:3 to 10:

5.

6. The method for preparing the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy according to claim 1, characterized in that: The molar ratio of nickel to 2,5-dimercaptoterephthalic acid in the mixed solution 3 of step (3) is 1:1 to 3:

1.

7. The method for preparing the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (4) is 120-160° C., and the time of the hydrothermal reaction is 2-5 hours.

8. The method for preparing the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy according to claim 1, characterized in that: The alkali in step (5) is potassium hydroxide; the concentration of the alkali ethanol solution is 0.35-0.75M, and the etching reaction time is 9-15h.

9. The D-NiFe / DMBD-Fc catalyst based on a double defect engineering strategy prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the D-NiFe / DMBD-Fc catalyst based on the dual defect engineering strategy as claimed in claim 9 in electrocatalytic oxygen production.

Citation Information

Patent Citations

  • Alkali-etched metal organic framework material, and application thereof in electrocatalytic decomposition of water

    CN110835767A

Cited By

  • MOF (Metal Organic Framework) material rich in coordination defects as well as preparation method and application of MOF material

    CN119978410A